Nonlinear elliptic partial differential equations : Workshop in celebration of Jean-Pierre Gossez's 65th birthday, September 2-4, 2009, Université libre de Bruxelles, Belgium - Workshop in Nonlinear Elliptic Partial Differential Equations; Bonheure, Denis; Cuesta, Mabel; Dozo, Enrique J. Lami; Takáč, Peter; Van Schaftingen, Jean; Willem, Michel; Gossez, J. P. (Contemporary mathematics, 2011)
This volume contains papers on semi-linear and quasi-linear elliptic equations from the worshop on nonlinear elliptic partial differential equations, in honour of Jean-Pierre Gossez's 65th birthday. The workshop reflected Gossez's contributions in nonlinear elliptic PDEs.